2020
DOI: 10.1186/s12876-020-01387-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genomic characteristics of mucosal signet-ring cell carcinoma in Helicobacter pylori-uninfected stomach

Abstract: Background: Gastric cancer develops even in Helicobacter pylori(H. pylori)-uninfected patients and its typical histological feature is signet ring cell carcinoma (SRCC) within the mucosal layer. However, the biological characteristics of SRCC remain unclear. We aimed to clarify the pathological and genetic features of SRCC in H. pylori-uninfected patients. Methods: Seventeen H. pylori-uninfected patients with mucosal SRCCs were enrolled and their clinicopathological characteristics were compared with those of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
(21 reference statements)
0
11
2
Order By: Relevance
“…The methylation rates in intramucosal DGCs were generally low, although they tended to be higher than those in the adjacent normal mucosa (data not shown). Recent genetic analysis of Hp-uninfected DGC reported that CDH1 mutations were found in only one of seven cases, in contrast to the high prevalence of CDH1 mutations observed in our study [42]. The low amount of input DNA (10 ng in every case) and the long period of paraffin embedding (median 6 years) may have affected the quality of the analysis, resulting in a low frequency of detection of CDH1 mutations [45].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The methylation rates in intramucosal DGCs were generally low, although they tended to be higher than those in the adjacent normal mucosa (data not shown). Recent genetic analysis of Hp-uninfected DGC reported that CDH1 mutations were found in only one of seven cases, in contrast to the high prevalence of CDH1 mutations observed in our study [42]. The low amount of input DNA (10 ng in every case) and the long period of paraffin embedding (median 6 years) may have affected the quality of the analysis, resulting in a low frequency of detection of CDH1 mutations [45].…”
Section: Discussioncontrasting
confidence: 89%
“…In addition to Hp infection, smoking has been reported to increase the risk of DGC compared to in non-smokers [39,40]. Previous studies reported that the prevalence of smoking was high in patients with Hp-uninfected DGCs [41,42]. However, SBS 4, the signature associated with smoking, was not observed in the present study (Fig.…”
Section: Discussioncontrasting
confidence: 61%
“…TogoVar is becoming recognized as shared infrastructure data. The purposes for its use are variant prioritization 34 , determination of whether a variant of interest is known or unknown 35 , and comparison of allele frequencies in TogoVar with those of disease groups or non-Japanese populations 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, gastric SRC often inflicts the younger females, who are more susceptible to having distant metastasis, leading to poor survival outcomes [ 3 ]. Gastric SRC usually has more aggressive biological behavior than other subtypes of adenocarcinoma [ 4 ]. The overall prevalence of gastric cancer has gradually decreased in recent years, but the incidence of gastric SRC is still rising [ 5 ], accounting for 35%–45% of gastric adenocarcinoma cases recently [ 6 ].…”
Section: Introductionmentioning
confidence: 99%